Digitgrasses - Carrol G. Chambliss; Martin B. Adjei; Lynn E. Sollenberger; Joao M. B. Vendramini; Yoana C. Newman (EDIS)
Revised! SS-AGR-51, a 4-page illustrated fact sheet by J. M. B. Vendramini, Y. C. Newman, and L. E. Sollenberger, describes these warm-season perennial grasses — cultivars, pasture establishment and maintenance, hay production, and insect control. Published by the UF Department of Agronomy, May 2009.